Association between behavioral and sociodemographic factors and high subjective health among adolescents: a nationwide representative study in South Korea - Jaehyun Kong; Seohyun Hong; Seunghwan Lee; Seokjun Kim; Soeun Kim; Jiyeon Oh; Wonwoo Jang; Hanseul Cho; Sooji Lee; Jiseung Kang; Yejun Son; Lee Smith; et al. (Scientific Reports)
Abstract The need to understand subjective health has increased during the COVID-19 pandemic, given its substantial impact on lifestyle habits and perceptions. Thus, this study aimed to investigate the trends and association of subjective health with demographic and behavioral factors, primarily focusing on the change when the COVID-19 pandemic emerged. This study used data from the Korea Youth Risk Behavior Web-based Survey, comprising 1,190,468 adolescents aged 12–18 years (female, 48.49%). We investigated the trends and association of subjective health with demographic and behavioral factors from 2006 to 2023. A weighted linear regression and joinpoint regression were conducted to evaluate the trend in adolescent subjective health, while logistic regression was used to assess associated factors. A stratification analysis was performed for subgroups to determine variations across different demographic and behavioral groups. The prevalence of reporting high subjective health increased throughout the years before the COVID-19 pandemic; however, subjective health exhibited a decreasing trend during the pandemic. Regarding demographic factors, female sex (ratio of odds ratio [ROR], 0.85 [95% CI, 0.83–0.87]), low-income households (ROR, 0.67 [95% CI, 0.64–0.69]), and low academic achievement (ROR, 0.83 [95% CI, 0.81–0.85]) were associated with less likelihood of reporting high subjective health. Healthier behavioral factors (ROR, breakfast consumption, 1.13 [95% CI, 1.10–1.16]; sufficient fruit intake, 1.12 [95% CI, 1.09–1.15]; sufficient physical activity, 2.02 [95% CI, 1.95–2.09]) were associated with higher subjective health, and the disparities increased during the COVID-19 pandemic. To address the observed decline in subjective health among adolescents during the COVID-19 pandemic, targeted interventions aimed at promoting healthy behaviors among particularly vulnerable demographics are crucial.